2010
DOI: 10.1111/j.1745-4514.2009.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content and Antioxidant Capacities of Parinari Curatelifolia, Strychnos Spinosa and Adansonia Digitata

Abstract: The phenolic content and antioxidant capacities of Parinari curatelifolia, Strychnos spinosa and Adansonia digitata were determined and compared to orange juice and baobab nectar, a commercial beverage. Methanolic extracts were investigated for their ability to scavenge free radicals by the 1, 1‐diphenyl‐2 picrylhydrazyl radical and superoxide radical scavenging assays whilst the β‐Carotene Linoleic Acid Model System and inhibition of phosholipid peroxidation were used as model systems. The reducing power assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Ndabikunze and co-workers (Ndabikunze et al, 2010) reported chemical composition of Vitex mombassae (smelly-berry), Adansonia digitata (baobab), Uapaca kirkiana (wild loquat) and Sclerocarya birrea (marula plum) indigenous fruits from various Miombo woodlands of Tanzania. Similar chemical composition were analaysed in Parinari curatelifolia, Strychnos spinosa and Adansonia digitata fruits from Buhera district of Zimbabwe (Nhukarume et al, 2010). These studies show wide variation in chemical composition including bioactive compounds within and among fruit species.…”
Section: Introductionsupporting
confidence: 68%
“…Ndabikunze and co-workers (Ndabikunze et al, 2010) reported chemical composition of Vitex mombassae (smelly-berry), Adansonia digitata (baobab), Uapaca kirkiana (wild loquat) and Sclerocarya birrea (marula plum) indigenous fruits from various Miombo woodlands of Tanzania. Similar chemical composition were analaysed in Parinari curatelifolia, Strychnos spinosa and Adansonia digitata fruits from Buhera district of Zimbabwe (Nhukarume et al, 2010). These studies show wide variation in chemical composition including bioactive compounds within and among fruit species.…”
Section: Introductionsupporting
confidence: 68%
“…(40) Protective effects of phytochemicals are because of their properties as free radical scavengers, hydrogen-donating compounds, singlet oxygen quenchers and or metal chelators. (41) Nhukarume et al (42) found S. spinosa had phenolic content radical quenching ability trends and flavonoids, expressed as catechin equivalence comparatively similar to baobab nectar. Proanthocyanidins, expressed as % leucocyanidin equivalence, were comparatively similar to mobola plum (Parinari curatellifolia).…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Indigenous fruit trees in Africa supplement the diet of many rural families by providing essential nutrients (Bille et al 2013;Nhukarume et al 2010) and serve as a livelihood source, especially in times of famine (Legwaila et al 2011;Mithöfer and Waibel 2003;Packham 1993). Hundreds of indigenous fruit species exist in Africa that are locally significant, although they might be unknown in global markets (Jamnadass et al 2011).…”
Section: Introductionmentioning
confidence: 99%